The influence of training and competition on sleep behaviour of soccer referees. Issue 1 (2nd January 2022) - Lastella, Michele; Miller, Dean J; Vincent, Grace E; Elsworthy, Nathan; Scanlan, Aaron T; Duffield, Rob
ABSTRACT: Objectives: The aims of the present study were to (1) quantify sleep behaviours of soccer referees and (2) compare sleep behaviours between nights before training,  before matches, and after matches. Methods: Fourteen professional soccer referees from the A-League (mean±SD; age 34 ± 4 years; sex: 11 males, 3 females) participated in this observational study. Referees' sleep behaviours were examined using sleep diaries and wrist activity monitors for 31 consecutive nights during the 2018–2019 A-League season. Separate linear mixed models were conducted to assess differences in sleep behaviours between nights before training, before matches, and after matches. Results: On average, referees did not obtain recommended sleep durations across the in-season (mean±SD sleep duration: 6.4 h ± 0.7 h). Referees went to bed later, spent less time in bed, and slept significantly less post-matches compared to pre-training and pre-match nights ( p < 0.05). Conclusions: Referees were particularly susceptible to inadequate sleep on nights following training and matches. The findings related to poor sleep behaviours highlight the importance of implementing monitoring systems to understand the sleep behaviours of referees, with further research encouraged to ascertain the efficacy of various sleep hygiene practices to optimise sleep in this population.